Kejutan Pertumbuhan Nilai Tukar Riil Terhadap Inflasi, Pertumbuhan Output, dan Pertumbuhan Neraca Transaksi Berjalan di Indonesia - Darwanto Darwanto (Economic Journal of Emerging Markets, 2007)
This paper examines the effect of real exchange rate growth shock on the Indonesia economic performance by considering quarterly data of inflation, output growth and current account growth. We use the estimated impulse response functions and variance decomposition of VAR model to investigate the response of Indonesia macroeconomic to real exchange rate growth shock. The empirical evidence indicates that fluctuation of real exchange rate growth shock effects inflation and output growth, but it can not affect current account growth. Moreover, the results from the analyses suggest that the real exchange rate depreciations is contractionary that contrary to classical wisdom.Keywords: VAR, impulse response function, variance decomposition.